Anti-Depressant Activity of the Leaves of Zanthoxylum Armatum on Swiss Albino Mice - Yadav, Chandrajeet Kumar; Poudel, Kamal; Mehta, Roshan; Shrivastava, Amit Kumar (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Depression is a global mental disorder that has high incidence, high recurrence, and high self-mutilation and suicide rates. Although the antidepressant drugs are available for the treatment, depression still continues to be a major medical problem. The present study was designed to study the anti-depressant activity of the leaves extract of Zanthoxylum armatum using forced swim test and tail suspension test (TST) on Swiss albino mice. MATERIAL AND METHODS The anti-depressant activity of the leaves of Zanthoxylum armatum was assessed using chronic unpredictable mild-stress (CUMS) induced depression in mice. The animals were treated with the methanolic extract of leaves of Zanthoxylum armatum orally at two doses of 100, 200 mg/kg body weight for eight days after (CUMS) induced depression in mice. RESULTS The data were analyzed by one-way ANOVA followed by tukey multiple comparison test. The leaves extract presented significant antidepressant activity in mice (p<0.05), CONCLUSION The results demonstrate that methanolic extract of leaves of Zanthoxylum armatum has got significant antidepressant activity.